Suggest training modules for the development of muscle strength and some skill traits of the football player - meftah medjadi; abderrzak faid; ameur.hamlaou (sports creativity, 2025)
this study aimed to find out whats the influence of suggested training units on the physical strenth evolution and some skilled features characteristies of a football player less than 16 years old when the researcher used an experimental method the total survey contains 26 players 20 of them have been chosen as a symbol to study as well 6 players were excheded and appointed by intentional survey which is divided into two homogeneous groups (teams) that symbol has been selected spontancously where as the used tools in this study used test of precision players ,arms strenth test ,arms quickness test, feet strenth test, feet quicknes test and the results were _ there are statistic differences in measuring before and after because _ the training units influenced the measure (after) _ training units are used for more than two units gives positive evolution to foot ball players _ there is a kend of Progress in the skill of passing and receiving for some members of the expiremental group comparing with the real group _ There is an evolution in physical strenth for the expiremental group comparing with the real group